Solitary Bone Plasmacytoma in the Sacrum (Revista de Medicina Clinica, 2023)
Clinical snapshot on "Solitary Bone Plasmacytoma in the Sacrum" presented in volume 7 issue 1 of 2023 of Revista de Medicina Clínica.
Keywords: Plasmacytoma; Sacrum